Peningkatan Pengetahuan KB Implan pada WUS di Desa Bandar Agung Wilayah Kerja Puskesmas Sribhawono - Siti Zulaikah; Evi Rianti; Vibri Fitri Agustin; Sri Lestari; Tri Yuni Handasari; Nila Qurniasih (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The main problem in Indonesia is the population growth rate which is still high with a percentage of 278.8 million in 2023. This problem can be prevented by using contraceptives that are effective and have long-term effects, one example is the use of birth control implants. Bandar Agung village is a village with a population of 17,000 people and consists of WUS. Based on data, the majority of the population still does not use long-term contraceptives, on average 70% of people prefer to use injectable contraceptives. One of the reasons for mothers' interest in using contraceptive implants is the mother's lack of knowledge about implants. So the solution offered to this problem is to provide education regarding implant contraception. The methods used in this activity are lectures, discussions and questions and answers. So with this activity, it is hoped that the community, especially women, will be able to understand and realize the importance of using family planning, one of which is implantable family planning and that there will be an increase in knowledge for WUS by 75%. With this program in the Puskesmas area, it is hoped that the community, especially women, can carry out implant contraception to reduce the high population growth rate